Somatic growth and gonadal development of Paracentrotus lividus (Lamarck, 1816) fed with diets of different ingredient sources - Lourenço, Sílvia (2021)
Sea urchins’ gonads are a delicacy highly appreciated worldwide. In Europe, Paracentrotus lividus is one of the most valuable edible sea urchin species and a desired target for aquaculture. One of the challenges of echinoculture is to increase the sea urchins’ growth rate during the on-growing phase and reducing the production cycle required to obtain sea urchins of commercial size (test diameter ≈ 50 mm). The present study aimed to evaluate the growth and gonad development of P. lividus urchins fed with three dry diets for 15 weeks. The diets were formulated with ingredients of three different sources: an algae-based, a fishmeal-based and a cereals-based diet. The somatic growth was assessed by biometric indicators like the linear and specific growth rates. The gonadal development was assessed by the gonadal somatic index (GSI), gametogenesis level, proximate composition and fatty acids profile. The results obtained showed high growth rates in all the three diets tested (0.44% per day). The sea urchins fed with the cereals diet presented the highest GSI (8.22%) with higher proportion of gonads in growing and premature stages. The proximate composition of the sea urchins’ gonads was significantly affected by diet and sea urchins’ sex, particularly the lipid content. Concomitantly, fatty acids (FA) profile of the gonads was influenced by both diet and sea urchins’ sex with saturated and polyunsaturated FA playing an important role in this differentiation.